Language learning is hands-on: Exploring links between infants’ object manipulation and verbal input - West, Kelsey L.; Iverson, Jana M. (Cognitive development, 2017)
•Infant object manipulation was examined in the home at 10, 12, and 14 months.•The relation between infant object manipulation and caregiver labeling was examined.•Caregiver utterances contained more labels during infant object manipulation.•Caregivers’ labels frequently corresponded to the infants’ held object and eye gaze.•Infants’ actions with objects yielded different verbal input from caregivers. Research demonstrates that object manipulation may provide infants’ with optimal sensory input for successful word learning to occur (Yu & Smith, 2012). Thus, it may be important to understand the relation between infant object manipulation and caregiver labeling in a naturalistic environment. The present study examined 13 parent-infant dyads longitudinally at 10, 12, and 14 months in their homes. The frequency and context of ideal labeling moments—wherein infants are holding and visually attending to an object when the label is presented—were examined. Results revealed that when infants were holding objects, caregivers’ verbal input was less frequent but contained a significantly greater proportion of labels relative to moments when infants were not holding objects. Additionally, ideal labeling moments were more likely to occur during particular infant actions than during passive holding alone. Findings have implications for understanding the role that manual motor behavior plays in infants’ early language environment.